The Ideal Model For Implementing A Proportional System in The 2024 Elections in Indonesia - Lili Istianah (Fakultas Hukum Dehasen, 2023)
The proportional system used in elections in Indonesia is divided into two systems: open and closed proportional. From 1955 to 1999 elections were held with a closed proportional system. Then from 2004 to 2019, open proportional elections were used. This research will discuss the advantages and disadvantages of the proportional system by actualizing it with the upcoming election system, namely the 2024 elections based on JR's rejection to the Constitutional Court because it is considered to be at home with the government system and the legislative system related to elections. If you return to using closed elections, it is feared that you will return to the past with an authoritarian government regime and kill democracy. The use of an open proportional election system is the best solution to be used in the 2024 elections. The method used in this research is qualitative research with the type of normative jurisprudence research. The data collection method uses argument with data sources in the form of documents, journals, papers and news in the media. The conclusion of this research lies in the use of open proportional to be the ideal system that can be used in the 2024 elections. If there is a change in the electoral system, it will change the entire order of the electoral system that has been made.